The coronavirus outbreak: the central role of primary care in emergency preparedness and response - Dunlop, C; Howe, A; Li, D; Allen, LN (Royal College of General Practitioners, 2020)
On the last day of 2019, a cluster of cases of a pneumonia with unknown cause were reported by the Chinese authorities to the World Health Organization (WHO), believed to be connected to a seafood market in Wuhan, China. This market was closed the following day. On 7 January 2020, a novel coronavirus was isolated, and known pathogens were ruled out.1 Coronaviruses usually cause respiratory illness ranging from the common cold to severe acute respiratory syndrome (SARS). Clinical symptoms and signs of the Wuhan coronavirus include fever, with some sufferers experiencing difficulty breathing and bilateral pulmonary infiltrates seen on chest X-ray. WHO are referring to it as ‘2019-nCov’. At the time of writing, there have been over 4,500 confirmed cases and 106 deaths, including among healthcare workers. Over 98% of these cases are within mainland China, but cases have also been confirmed in tens of other countries.